To solve the equation -7(8x+5) = 5x+10, we need to distribute and simplify.
Starting with -7(8x+5), we get -56x - 35.
So the equation becomes -56x - 35 = 5x + 10.
To isolate the x variable, we can add 56x to both sides of the equation:
-56x - 56x - 35 = 5x + 56x + 10.
Simplifying further, we get -112x - 35 = 61x + 10.
Next, we can add 35 to both sides:
-112x - 35 + 35 = 61x + 10 + 35.
Simplifying gives -112x = 61x + 45.
To eliminate the x term on the right side, we can subtract 61x from both side:
-112x - 61x = 61x + 45 - 61x.
Simplifying gives -173x = 45.
Finally, to solve for x, we divide both sides by -173:
(-173x)/(-173) = 45/(-173).
Simplifying gives x = -45/173.
Therefore, the solution to the equation -7(8x+5) = 5x+10 is x = -45/173.
−7(8x+5)=
5x+10
Answer
Attempt 3 out of 3
The equation has
one solution
and it is x, equalsx=
.
1 answer